Gender Role Transformation in Village Forest Management Through Digital Applications: a Case Study of Village Forest Management Institution - Herna, Herna; Kolopaking, Lala M; Hapsari, Dwi Retno (Jurnal AGRISEP, 2026)
This study departs from the observation of the use of digital applications in village forest management, where women are more active in data collection and communication, reflecting the beginning of gender role transformation in village forest management in Kuala Indragiri Sub-district, Indragiri Hilir District. It investigates how digitalization affects women’s participation in village forest management institutions (VFMI) and how sociocultural norms shape the gender digital divide. Using a mixed-methods case study in two mangrove coastal villages - Sapat and Sungai Piyai Village - the research combines surveys, in-depth interviews, participant observation, meaning that the higher the gender digital divide, the lower the role of women in institutions. Men dominating technical applications such as Avenza Maps (mapping), while women limited to administrative or communication tools WhatsApp and KoboToolbox (online surveys). Although limited, women's involvement in training and the use of digital applications is beginning to open space for recognition of their strategic role in village forest governance, reflecting the potential for gender transformation. Affirmative and intersectional strategies are needed, to minimize the reproduction of existing gender gaps. This study contributes to the discourse on inclusive digital transformation by highlighting the importance of overcoming structural and cultural barriers in social forestry programs. The findings also have the potential to be replicated in other coastal communities that face similar challenges in digitalization and gender inequality.